Case Report: Dual-chamber pacemaker for hypertrophic cardiomyopathy with bradyarrhythmia and idiopathic pericardial effusion: a report of two cases and literature review - Liu, Chang; Zheng, Fei; Gao, Yuxia; Wang, Zheming; Zhang, Xinyu; Tian, Xiuqing (Frontiers in Cardiovascular Medicine, 2025)
BackgroundHypertrophic cardiomyopathy (HCM) is an autosomal dominant disorder characterized by asymmetric hypertrophy of the ventricles and the ventricular septum, leading to subsequent left ventricular outflow tract (LVOT) obstruction and diastolic dysfunction. Typically, patients with HCM experience sinus tachycardia and sinus arrest relatively infrequently. In addition, the concurrent occurrence of HCM with non-surgically induced (ablation or myectomy) bradyarrhythmia and idiopathic pericardial effusion in adult patients has not been previously reported.Case summaryIn this report, we present two elderly female patients with HCM who exhibited sinus bradycardia and sinus arrest, one of whom also presented with moderate pericardial effusion, they all presented with chest tightness. To manage the complex comorbidities, we opted for dual-chamber pacemaker implantation. Subsequent examinations and follow-up revealed that pacing significantly reduced LVOT obstruction and corrected heart rhythm. Additionally, there was no significant progression of pericardial effusion.DiscussionThe primary strategies for alleviating LVOT obstruction involve altering the structure of the septum, including septal myectomy (SME), alcohol septal ablation (ASA), and septal radiofrequency ablation. Meanwhile, a dual-chamber pacemaker can treat HCM by changing the sequence of myocardial contraction. Although pacemakers have been considered an inferior alternative due to their relatively large residual obstruction, their benefits may be significantly underestimated. This report underscores the additional efficacy of dual-chamber pacemakers in managing HCM, particularly in patients complicated by sinus node dysfunction and idiopathic pericardial effusion.